Pemenuhan Hak-Hak Pekerja Anak Oleh Orang Tua di Kota Pekalongan: Perspektif UU Perlindungan Anak No. 23 Tahun 2002 dan Maslahah Al-Mursalah - Oliviawan, Deva (Al-Hukkam: Journal of Islamic Family Law, 2021)
One of the problems regarding children in Pekalongan City is child labor, the parties who are fully obliged to fulfill children's rights are parents, and so that the implementation can run well it needs to be adjusted to the Child Protection Law no. 23 of 2002 and maslahah al-mursalah. This study aims to determine the fulfillment of child labor rights in the city of Pekalongan and the perspective of the Child Protection Act no. 23 of 2002 and maslahah al-mursalah. The results showed that some parents in the city of Pekalongan mostly understood the rules and fulfillment of children's rights, but in practice there were still parents who did not fulfill the provisions contained in the Child Protection Law no. 23 of 2002 and maslahah al-mursalah. So it can be said that the fulfillment of the rights of child labor in the city of Pekalongan by parents has not been carried out properly because of these shortcomings.